A deadlock-free dimension order routing for hierarchical 3D-mesh network - Rahman, M.M. Hafizur; Shah, Asadullah; Inoguchi, Yasushi (2012)
Virtual channels are used to make the routing algorithm deadlock-free for a wormhole routed network, however, its unconstrained used is strictly prohibited for the cost-effective parallel computers. In this paper, we present a deadlock-free routing algorithm for the Hierarchical 3D-Mesh (H3DM) network using 2 virtual channels – 2 being the minimum number for dimension-order routing – and evaluate the network’s dynamic communication performance using the proposed routing algorithm under the uniform traffic pattern. We evaluate the dynamic communication performance of H3DM, mesh, and torus networks by computer simulation. It is shown that H3DM network yields low average transfer time than that of mesh and torus networks. The trade-off between throughput and latency of these network shown that H3DM network provide better dynamic communication performance than that of mesh and torus networks before saturation.